Remote prognosis after primary cesarean delivery: the association of VBACs and recurrent cesarean deliveries with maternal morbidity - Erez O; Novack L; Kleitman-Meir V; Dukler D; Erez-Weiss I; Gotsch F; Mazor M (Dove Medical Press, 2012)
Offer Erez1, Lena Novack2, Vered Kleitman-Meir1, Doron Dukler1, Idit Erez-Weiss3, Francesca Gotsch4, Moshe Mazor11Department of Obstetrics and Gynecology, Soroka University Medical Center, 2Department of Epidemiology, 3Department of Family Medicine, Faculty of Health Sciences, Ben-Gurion University of the Negev, Beer-Sheva, Israel; 4Obstetrics and Gynecology Departement, Policlinico GB Rossi Azienda Ospedaliera Universitaria Integrata Verona, ItalyPurpose: To determine the effects of vaginal birth after cesarean (VBAC) versus repeated cesarean sections (RCS) after a primary cesarean section (CS), on the rate of intraoperative and postpartum maternal morbidity.Patients and methods: This is a retrospective population-based cohort study. During the study period (1988–2005) there were 200,012 deliveries by 76,985 women at our medical center; 16,365 of them had a primary CS, of which 7429 women delivered a singleton infant after the primary CS, met the inclusion criteria, were included in our study, and were followed for four consecutive deliveries. Patients were divided into three study groups according to the outcome of their consecutive delivery after the primary CS: VBAC (n = 3622), elective CS (n = 1910), or an urgent CS (n = 1897). Survival analysis models were used to investigate the effect of the urgency of CS and the numbers of pregnancy predating the primary CS on peripartum complications.Results: Women who failed a trial of labor had a higher rate of uterine rupture than those who had a VBAC. Patients who delivered by CS had a higher rate of endometritis than those giving birth vaginally. The rate of cesarean hysterectomy and transfer to other departments increased significantly at the fourth consecutive surgery (P = 0.02 and P = 0.003, respectively). VBAC was associated with a 55% reduction in the risk of intrapartum complications in comparison to a planned CS (hazard ratio [HR] 0.45; 95% confidence interval [CI]: 0.22–0.89. A greater maternal parity at the time of primary CS was associated with lower intrapartum and postpartum morbidities (HR 0.44; 95% CI: 0.24–0.79; HR 0.54; 95% CI: 0.47–0.62, respectively).Conclusions: (1) A successful VBAC is associated with a reduction in the intrapartum complications; and (2) maternal morbidity increases substantially from the fourth consecutive cesarean delivery.Keywords: trial of labor, uterine rupture, hysterectomy, blood transfusion, parity